Implementation of the Wahdah Method in Improving Students' Ability to Memorize the Qur'an - Nofika Ria Nur Farida; Muhammad Anas Ma`arif; Ari Kartiko (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article aims to analyze and explain: Planning, implementing, and evaluating the wahdah method in improving the ability to memorize the Qur'an in junior high school students based on the Amanatul Ummah Islamic Boarding School. This article uses a qualitative approach with the type of case study research. Data was collected by using field observation, interview, and documentation techniques. Data analysis techniques include data collection, data presentation, and data verification. From the analysis of research data, the results of this article are as follows: (1) the planning of the wahdah method in the Amanatul Ummah Islamic Boarding School-Based Junior High School is the division of groups or class divisions according to their abilities. (2) implementation of the wahdah method helps make it easier for students to memorize by reading verses of the Qur'an with tartil repeatedly, memorizing verse by verse and tarqiq. (3) The evaluation is that if students memorize one juz, they will be tested with an ustadz/ustadzah other than their class supervisor. The next research recommendation is about the strategy of implementing the wahdah method with a comparison of taqrir, murojaah will result in better memorizing the Qur'an.